Genetic and treatment‐related risk factors associated with external apical root resorption (EARR) concurrent with orthodontia. (April 2015) - Sharab, L. Y.; Morford, L. A.; Dempsey, J.; Falcão‐Alencar, G.; Mason, A.; Jacobson, E.; Kluemper, G. T.; Macri, J. V.; Hartsfield, J. K.
Structured Abstract: Objective: As genetic variation accounts for two‐thirds of the variation in external apical root resorption (EARR) concurrent with orthodontic treatment, we analyzed the association of selected genetic and treatment‐related factors with EARR concurrent with orthodontic treatment. Setting and sample population: This case–control study of 134 unrelated, orthodontically treated Caucasian individuals was conducted in part at an Indiana Private Practice, Indiana University and the University of Kentucky. Methods: Utilizing a research data bank containing information from 1450 orthodontically treated patients, pre‐ and post‐treatment radiographs from 460 individuals were evaluated for EARR of the four permanent maxillary incisors. Sixty‐seven unrelated Caucasians with moderate to severe EARR were identified and were age‐/sex‐matched with orthodontically treated Caucasian controls yielding 38 females and 29 males per group. Factors tested for an association with EARR included the following: 1) treatment duration, 2) extraction of maxillary premolars, 3) numerous cephalometric measurements, and 4) DNA polymorphisms within/near candidate genes in a pathway previously implicated in EARR such as the purinergic‐receptor‐P2X, ligand‐gated ion channel 7 ( P2RX7; rs208294, rs1718119, and rs2230912), caspase‐1 ( CASP1 ; rs530537, rs580253, and rs554344), interleukin‐1 beta ( IL1B; rs1143634), interleukin‐1 alpha ( IL1A; rs1800587), and interleukin‐1 receptor antagonist ( IL1RA ; rs419598) genes. Stepwise logistic regression was utilized to identify the factors significantly associated (significance taken at or less than the layered Bonferroni correction alpha) with the occurrence of EARR. Results: A long length of treatment and the presence of specific genotypes for P2RX7 SNP rs208294 were significantly associated with EARR. Conclusion: EARR occurrence was associated with both genetic and treatment‐related variables, which together explained 25% of the total variation associated with EARR in the sample tested.